Bite Force Evaluation in Unilateral Posterior Crossbite Patients - Maitham G. Oudah1,/ Hayder F. Saloom. 2 ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
The maximum bite force (MBF) refers to the highest force exerted by an individual during the fragmentation of food, which is closely associated with the process of mastication. Many studies showed that malocclusions frequently exhibit an association with diminished maximal bite force. Furthermore, Occlusion may contribute to mental disorder such as anxiety, tension, Alzheimer's, and senile dementia. Aim: The current study aimed to assess the difference in maximum bite force between the sides of the jaw in cases of unilateral posterior crossbite. Methods: Sixty patients were chosen, and they were split into two groups: a group of teeth unilateral posterior crossbite and one tooth posterior crossbite group. The maximal bite force for each patient is recorded for each side and compared with the other side in the same group and between two groups. Results: the result shows a significant difference between sides in a group of teeth unilateral posterior crossbite (P=0.007) and a non-significant difference between sides in single tooth posterior crossbite (P=0.365). Between the groups, the crossbite side shows a significant difference (P=0.010) while the non-crossbite side shows a non-significant difference(P=0.160). Conclusion: There exist variations in bite force between cases involving numerous teeth in posterior crossbite as opposed to those involving a single tooth. There is no discernible variation observed among the groups with regard to the normal side, in contrast to the crossbite side.